INTEGRAL MODEL OF THE DESIGNER’S PERSONAL BRAND - Удріс-Бородавко, Н.С.; Гордійчук , Я.Ю. (Art and Design, 2024)
Purpose. The purpose of the article is to systematize and organize expert advices for the formation of a designer’s personal brand and combine them into a holistic recommendation model. Methodology. To achieve the tasks, the method of systematic analysis of theoretical materials and practical recommendations in the field of social psychology, communication, imagology and marketing, as well as the method of synthesis to form the final model was used. Results. It has been found that scientific analytics of personal branding focuses on conceptual components such as social mission, social responsibility, authenticity, image, while expert recommendations focus on specific goals of attracting new customers, with a focus on demonstrating experience in design, uniqueness of cooperation with the client, and the character of work. The combination of different approaches made it possible to form a holistic model for building a designer’s personal brand. Its main components are: defining a goal or a set of goals that comply with the SMART model and represent the level of social responsibility of the designer and the level of his or her personal benefit in the form of commissioned projects; forming a unique offer that meets the functional (designer’s experience), social (belonging to a community of designer’s fans), mental (gaining new knowledge about design in the designer’s own presentation) and spiritual (social responsibility initiatives) expectations of the target group; definition of the target audience (conditional portraits of ideal clients and supporters of various aspects of the designer’s uniqueness); selection of a system of visual and verbal identifiers (characteristic portrait features, costume, kinesics, identity, objects, special permanent phrases). The article also suggests variable means of content for the model components based on expert advice. Scientific novelty. The scientific novelty is the creation of a unified model of personal brand for the designer, taking into consideration current recommendations from experts. Practical significance. The practical significance lies in the possibility of applying the model by designers to improve their own design practice, as well as, due to the coverage of target groups, to increase the influence of the design institution on social processes.